Association of sex hormone-binding globulin and dyslipidemia with Japanese postmenopausal women: a cross-sectional study - Takahiro Ichikawa; Hiroshi Okada; Masahide Hamaguchi; Megumi Hara; Naoyuki Takashima; Sadao Suzuki; Shiroh Tanoue; Yasufumi Kato; Mako Nagayoshi; Takashi Tamura; Michiaki Fukui; Keitaro Matsuo (Lipids in Health and Disease)
Abstract Background In postmenopausal women, lower levels of sex hormone-binding globulin (SHBG) have been linked to various metabolic conditions. The association between SHBG levels and the presence of dyslipidemia was investigated in comparison with other sex hormones. Methods Data from 570 postmenopausal women were analyzed. To assess the relationship between circulating sex hormone concentrations and dyslipidemia, logistic regression and receiver operating characteristic (ROC) curve analyses were performed to assess the relationships. Results Participants had a median age of 51.0 years (49.0–53.0). The multivariate analysis revealed that SHBG levels were significantly associated with dyslipidemia. Specifically, low SHBG levels correlated with hypertriglyceridemia and low high-density lipoprotein levels. The area under the curve (AUC) and the optimal SHBG level cutoff value for identifying the presence of dyslipidemia were 0.626 and 69.0 nmol/L, respectively. The AUCs for SHBG levels were highest for estradiol (E2), total testosterone (TT) and dehydroepiandrosterone sulfate (DHEAS) levels. Conclusions SHBG levels were significantly associated with dyslipidemia in postmenopausal women and outperformed E2, TT, and DHEAS levels. These findings highlight SHBG as a potential biomarker for dyslipidemia risk in postmenopausal women, warranting further research into its prognostic utility.